2012
DOI: 10.1097/pec.0b013e318258ad76
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access and Electronic Communication Among Families in an Urban Pediatric Emergency Department

Abstract: In this predominantly minority and economically disadvantaged population of caregivers presenting to an urban pediatric ED, a large majority reported regular access to the Internet and willingness and ability to receive communication from the ED via electronic means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Saidinejad et al noted that half of caregivers in an urban underserved pediatric ED were interested in receiving discharge information electronically with e-mail being the preferred modality. 4 Similar mechanisms could be used to distribute clinic discharge information, follow-up reminders, or additional preventive or acute care-based anticipatory guidance. Digital platforms also offer the possibility of bidirectional communication, providing a means with which clinicians could respond efficiently to patient or family queries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saidinejad et al noted that half of caregivers in an urban underserved pediatric ED were interested in receiving discharge information electronically with e-mail being the preferred modality. 4 Similar mechanisms could be used to distribute clinic discharge information, follow-up reminders, or additional preventive or acute care-based anticipatory guidance. Digital platforms also offer the possibility of bidirectional communication, providing a means with which clinicians could respond efficiently to patient or family queries.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,12 As an example, caregivers seeking care for their children in an inner-city ED were interested in receiving discharge information electronically. 4 An adult patient study demonstrated interest in having links to credible Web sites provided as part of their discharge paperwork. 18 Thus, medical providers could play an important role in connecting patients and families to credible resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many underserved patients report high rates of Internet access and wanting to communicate with health providers via e-mail to enhance health care decisions. [76][77][78][79][80] Some patients may have concerns about trust and privacy that could be worsened by real or perceived stigma in visit notes. 71,74,81 For example, in a Veterans Affairs shared notes study, some patients took issue with the way their clinicians described them.…”
Section: Ehr: Patient Portals and Shared Visit Notesmentioning
confidence: 99%
“…17 This affords opportunities for web-based tools to inform decision making regarding when and where to seek health care. We performed this pilot study to determine if a prototype SORT for Kids could be easily understood and used by parents and adult caregivers across a range of educational, racial, and ethnic backgrounds.…”
Section: Commentmentioning
confidence: 99%